The Relationship between Nutritional Knowledge and Compliance with Fe Tablet Consumption with the Incidence of Anemia - Hesty Aprianti Ratuk Tallama; Indanah Indanah; Muhammad Ridwanto (Indonesian Journal of Global Health Research, 2026)
Anemia that occurs in adolescents can cause the impact of physical growth delays, behavioral and emotional disorders. When the condition is acute, anemia can lead to death. and increase the risk of disorders during pregnancy later. Knowledge of anemia and adherence to taking low Fe tablets are one of the important factors in the incidence of anemia. The purpose of this study is to analyze the relationship between nutritional knowledge and compliance with Fe tablet consumption and the incidence of anemia in adolescent girls in the working area of the Karas Health Center, Fakfak Regency in 2025. This type of research uses a survey  research method with a quantitative approach with a cross sectional  research design.This research was conducted in the working area of the Karas Health Center, Fakfak Regency from June to July 2025. The sample in this study amounted to 81 adolescents were selected with purposive sampling. The population of this study is all adolescents aged 12-18 years in the Karas health center area. The independent variables are knowledge and compliance. The dependent variable is the anaemia of the body. The data were collected by questionnaire and haemoglobin test. Analysis using chi square. Chi Square analysis showed that there was a significant relationship between adherence to taking blood plus tablets and the incidence of anemia p value <0.001 (< 0.05). The results of the study showed that there was a significant relationship between knowledge about nutrition and the incidence of anemia p value <0.001 (< 0.05). The higher the knowledge of a teenager, the more anemia will be avoided. The more obediently a person takes Fe tablets, the more they avoid anemia.